Rapid and Accurate Identification of Candida albicans Isolates by Use of PNA FISH(Flow) - Trnovsky, Jan (American Society for Microbiology (ASM), 2008)
We developed the simple, rapid (1 h), and accurate PNA FISH(Flow) method for the identification of Candida albicans. The method exploits unique in solution in situ hybridization conditions under which the cells are simultaneously fixed and hybridized. This method facilitates the accurate identification of clinical yeast isolates using two scoring techniques: flow cytometry and fluorescence microscopy.